Medium-chain triglycerides/long-chain triglycerides versus long-chain triglycerides in treatment of cancer patients with major body mass loss. Survival in patients with refractory cachexia - Szefel, Jarosław; Kruszewski, Wiesław J.; Szajewski, Mariusz; Ciesielski, Maciej; Sobczak, Ewa; Czerepko, Maksymilian; Łysiak-Szydłowska, Wiesława (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Currently there are no established guidelines regarding the use of long-chain triglycerides (LCT) vs. medium-chain triglycerides medium-chain triglycerides (MCT)/long-chain triglycerides (LCT) in total parenteral nutrition (TPN). Severe malnutrition of patients with refractory cachexia (RC) often causes their disqualification from invasive methods of treatment thus decreasing their quality of life and survival time. Aim: Our study had two aims: to compare the changes in nutritional state of patients with RC receiving PN with LCT and LCT/ MCT lipid emulsions and to assess the influence of enteral nutrition on their survival time. Material and methods: The study group comprised of 50 patients (23 female, 27 male) with a median age of 66 years. Refractory cachexia was diagnosed in them due to dysphagia secondary to solid tumours causing obstruction of the gastrointestinal tract (GT). All patients were qualified for surgical gastrostomy due to contraindications to percutaneous endoscopic gastrostomy. The patients were randomly assigned into one of two groups and perioperatively received either LCT or LCT/MCT. Blood samples were collected four times and tested for: total protein, albumin, prealbumin, and C-reactive protein concentration. Patients received Home Enteral Nutrition after discharge from hospital. Results: Changes in nutritional status parameters were similar among patients receiving lipid emulsions LCT vs. MCT/LCT in TPN for 11 days. The mean survival time of all patients operated to gain enteral access to nutrition was 192 ±268 days, and the median survival was 98 days. Conclusions : Regarding the short-term TPN, the results of the study do not demonstrate any superiority of MCT/LCT lipid emulsions over LCT, or vice versa. The inability to eat significantly accelerates unintended body mass loss among patients with RC. Disqualification from invasive treatment options deprives some patients of the benefits they might have obtained from the surgical access to GT and enteral nutrition.